The HIP1 binding site is required for growth regulation of the dihydrofolate reductase gene promoter. - Means, A L (1992)
The transcription rate of the dihydrofolate reductase (DHFR) gene increases at the G1/S boundary of the proliferative cell cycle. Through analysis of transiently and stably transfected NIH 3T3 cells, we have now demonstrated that DHFR promoter sequences extending from -270 to +20 are sufficient to confer similar regulation on a reporter gene. Mutation of a protein binding site that spans sequences from -16 to +11 in the DHFR promoter resulted in loss of the transcriptional increase at the G1/S boundary. Purification of an activity from HeLa nuclear extract that binds to this region enriched for a 180-kDa polypeptide (HIP1). Using this HIP1 preparation, we have identified specific positions within the binding site that are critical for efficient protein-DNA interactions. An analysis of association and dissociation rates suggests that bound HIP1 protein can exchange rapidly with free protein. This rapid exchange may facilitate the burst of transcriptional activity from the DHFR promoter at the G1/S boundary.